The benefits of fully electronic consent management and consent collection via a tablet PC in supporting time-critical pandemic research—an example from a NAPKON COVID-19 project - Stahl, Dana; Rau, Henriette; Blumentritt, Arne; Fiedler-Lacombe, Lizon; Heim, Ekaterina; Valentin, Heike; Bialke, Martin; Kraus, Monika; Hoffmann, Wolfgang (Frontiers in Digital Health, 2025)
ObjectiveA study participant's informed consent, based on study information and expressed using a consent form (CF), is the ethical and legal basis for research with humans. Timely automatic access to a participant’s consent status in different systems is crucial for knowing which medical data, images, and biological samples can be collected for research. To support time-critical (pandemic) research, this article evaluates a fully electronic consent management system and a consent collection process using a tablet PC in comparison to traditional paper-and-pencil-based approaches and assesses their impact on patient recruitment.Materials and methodsThe evaluation is based on a COVID-19 study [the Sektorenübergreifende Plattform (SÜP) study; 2,753 study participants] that offered both paper-and-pencil- and tablet-based consent collection approaches and focused on the following: (a) initial CF validity and its impact on patient recruitment, (b) time-to-initial availability of structured consent information for other systems, (c) time-to-research based on completed quality assurance of CFs, and (d) feedback on both approaches from study staff and participants.ResultsThe initial CF validity increased significantly from 67.38% for paper-and-pencil-based CFs to 99.46% for tablet-based CFs. This quality increase also reduced the number of invalid CFs or CFs requiring corrections, which can lead to study exclusion and, consequently, lower recruitment rates and lost research data. The time lag between recruitment and the availability of data decreased significantly when using tablet-based CFs, supporting time-critical research while protecting participants’ privacy. Overall, the participants’ and study staff's feedback on tablet-based CF collection was positive and highlighted the benefits of tablet-based CF collection in reducing the documentational burden on study staff and enabling participants to adjust the CF’s appearance, for example, by choosing a bigger font size.DiscussionAlthough tablet-based CF collection has measurable positive effects, especially on patient recruitment rates due to an increase in initially valid CFs, the majority of the National Pandemic Cohort Network (German: Nationales Pandemie Kohorten Netz, NAPKON) study sites still solely use paper-and-pencil-based processes. Since the feedback from study staff and participants was mainly positive, other barriers beyond technical availability and workflows likely exist and need to be evaluated in further settings.ConclusionFully electronic informed consent collection is the “best practice” approach to ensure valid CFs and increase initial patient inclusion rates in studies. Due to the additional benefits, including shorter time-to-research, electronic consent form collection should be integrated into pandemic response schemes and other time-critical research.